Youth participation in smallholder livestock production and marketing - Mutua, Edna N.; Bukachi, S.; Bett, Bernard K.; Estambale, B.B.A.; Nyamongo, I. (Institute of Development Studies, 2017)
Agriculture is a leading source of employment for rural populations in Kenya. Through a mixed methods approach, this study sought to investigate youth participation in smallholder livestock production and marketing in Baringo County. The specific focus is on how social norms and micropolitics enable or constrain participation of particular groups of young people. The study established that personal choice, preference for paid over unpaid labour and gender norms in asset access, ownership and control influence smallholder participation in livestock production and trade. This shows a disconnect between Kenya's youth policy which advocates for equitable distribution of employment opportunities and the reality at community level. Interventions that seek to improve livestock production and marketing, particularly involving young people, should therefore adopt strategies that recognise these norms as a first step to addressing social exclusion.